Clinical studies of a new non-ionic contrast medium--iohexol (Omnipaque)--in patients sensitive to ionic contrast medium - Fuse, H (Hinyokika kiyo. Acta urologica Japonica, 1989)
Iohexol was used on 62 patients who had had side effects or adverse reactions to conventional ionic contrast medium. No side effects were observed. Iohexol provided better nephrographic and pyelographic effects, but in one case a diagnosis could not be made using 20 ml of Iohexol 300. Iohexol 350, 20 ml, was thought to be more suitable contrast medium than Iohexol 300, 20 ml, for ordinary intravenous pyelography. Iohexol could be used safely in patients with previous adverse reactions to ionic contrast media